The Truth Behind British Politeness - Peixoto, Rafael Marcos Tort (BELT - Brazilian English Language Teaching Journal, 2014)
The purpose of this paper is to analyse a chart published by the British newspaper The Telegraphabout the most common misunderstandings foreigners face while making use of English as their second language. L2 speakers are said to take every word at face value and therefore making some pragmatic mistakes. Sometimes there can be another meaning behind the spoken words, like it is unsaid for a reason. The pragmatics theories of irony in Attardo (1999) shed light on these translating and intercultural awareness issues by explaining what is behind the misunderstanding which is the secret ofthe so famous British politeness. Some considerations will be made upon the chart so as to understand it, such as an analysis of irony and native speakers’ perspectives on it. In addition to that, we will take into account the opinion of some native speakers of English to unveil some details and clarify how meaningful some sentences may be and if the researched chart is actually accurate.